Air and surface contamination by SARS-CoV-2 virus in a tertiary hospital in Wuhan, China. (October 2020) - Tan, Li; Ma, Boyi; Lai, Xiaoquan; Han, Lefei; Cao, Peihua; Zhang, Junji; Fu, Jianguo; Zhou, Qian; Wei, Shiqing; Wang, Zhenling; Peng, Weijun; Yang, Lin; et al.
Highlights: Twelve air samples and 355 surface samples from a hospital were tested for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Only one air sample, which was obtained during an intubation procedure, tested positive. A low level of surface contamination was found, and most occurred on high-touch surfaces. No association was found between surface contamination and patient characteristics. Abstract: Background: Few studies have explored air and surface contamination by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in healthcare settings. Methods: Air and surface samples were collected from the isolation wards and intensive care units designated for coronavirus disease 2019 (COVID-19) patients. Clinical data and the results of nasopharyngeal specimen and serum antibody testing were also collected for the patient sample. Results: A total of 367 air and surface swab samples were collected from the patient care areas of 15 patients with mild COVID-19 and nine patients with severe/critical COVID-19. Only one air sample taken during the intubation procedure tested positive. High-touch surfaces were slightly more likely to be contaminated with SARS-CoV-2 RNA than low-touch surfaces. Contamination rates were slightly higher near severe/critical patients than near mild patients, although this difference was not statistically significant ( p > 0.05). Surface contamination was still found near the patients with both positive IgG and IgM. Conclusions: Air and surface contamination with viral RNA was relatively low in these healthcare settings after the enhancement of infection prevention and control. Environmental contamination could still be found near seroconverted patients, suggesting the need to maintain constant vigilance in healthcare settings to reduce healthcare-associated infection during the COVID-19 pandemic.